A 5-year longitudinal study of the adolescent reinforcement sensitivity as a risk factor for anxiety symptoms in adulthood: Investigating the indirect effect of cognitive emotion regulation. (June 2016) - Izadpanah, Shahrzad; Schumacher, Maren; Bähr, Alessandra; Stopsack, Malte; Grabe, Hans Jörgen; Barnow, Sven
Abstract: This study investigated the longitudinal effects of the Behavioral Inhibition System (BIS) and the Behavioral Activation System (BAS) on anxiety symptomatology and tested the indirect effect of cognitive emotion regulation as a possible mechanism underlying this link. In this study, 274 individuals were assessed two times (T1 and T2 ), at a 5-year interval. We found an excellent fit for the hypothesized model, with BIS (T1 ) predicting both maladaptive cognitive emotion regulation (mCER) and T2 -anxiety even after controlling for T1 -anxiety. Further, mCER significantly mediated the relationship between BIS and T2 -anxiety, and between T1 -anxiety and T2 -anxiety. However, an alternative model, supposing that BIS and T1 -anxiety indirectly affect mCER through T2 -anxiety, showed a similar fit. While BAS predicted higher levels of adaptive cognitive emotion regulation (aCER), it was unrelated to mCER and showed a small positive association with anxiety only at higher levels of BIS. These findings provide longitudinal support for BIS as a risk for anxiety symptoms and support the importance of targeting mCER in the prevention and treatment of anxiety, especially among individuals with BIS sensitivity. Finally, the results suggest a possible overlap between anxiety and mCER that requires further longitudinal research to clarify the direction of their relationship. Highlights: We tested BIS/BAS as predictors of anxiety and ER. BIS predicted higher levels of anxiety and maladaptive ER over five years. Maladaptive ER mediated BIS-anxiety link. Similar fit for a second model with anxiety mediating BIS–maladaptive ER link BAS predicted higher anxiety scores only at higher levels of BIS.